Clinical significance of incidental common bile duct dilatation in children: A 10-year single medical center experience - Wan-Hsin Su; Hsun-Chin Chao; Mi-Chi Chen; Ming-Wei Lai; Chien-Chang Chen; Pai-Jui Yeh (Biomedical Journal)
Background: With the widespread use of abdominal ultrasonography (US), incidental detection of common bile duct (CBD) dilatation is common in pediatric populations. This study investigated the causes and clinical significance of CBD dilatation in children without biliary symptoms, jaundice, or causative lesions in US. Methods: We retrospectively reviewed pediatric patients with CBD dilatation from July 2013 to June 2023. All cases were detected via abdominal US. We analyzed the patients’ clinical manifestations, laboratory data, diagnosis, underlying diseases, and clinical course. Results: In a total of 687 patients enrolled, 338 met inclusion criteria (90 in hepatobiliary, 248 in CBD dilatation group). Of 128 patients with incidental CBD dilatation who underwent regular US examinations, 91 (71.1%) experienced resolution during follow-up. The proportion of patients with intrahepatic duct dilatation was significantly higher in the non-resolution group (p = 0.038). General health examination group had significant smaller CBD diameter compared to the gastrointestinal and infection groups. Correlation analysis found starting point of resolution decline at 3.24 mm (all-inclusive) and 2.51 mm (infant group) CBD diameter. Conclusions: Most children with incidental CBD dilatation did not have abnormal hepatobiliary function or other sonographic abnormalities. They usually remained asymptomatic and experienced uneventful clinical courses.